1995
DOI: 10.1183/09031936.95.08122088
|View full text |Cite
|
Sign up to set email alerts
|

Facial cooling, but not nasal breathing of cold air, induces bronchoconstriction: a study in asthmatic and healthy subjects

Abstract: Reflex-mediated bronchoconstriction in cold climates may be more important than it has previously been thought. This issue has seldom been studied using physiological methods. We wanted to investigate, using physiological methods, what triggers the bronchoconstriction occurring at cold ambient temperature during resting nasal ventilation: cooling of the skin of the face or cooling of the nasal cavity. Three experiments were carried out in 15 stable asthmatics and 10 healthy volunteers: 1) a whole-body exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 16 publications
2
53
2
Order By: Relevance
“…This again highlights the physiological nature of the reflex responses to cold air. However, other investigators have not detected any changes in FEV 1 in response to nasal breathing of subfreezing air (20,23). This discrepancy may reflect different methods to cool the nose and to measure the bronchoconstriction.…”
Section: Cold Air-provoked Lower-airway Reflex Responsesmentioning
confidence: 80%
See 2 more Smart Citations
“…This again highlights the physiological nature of the reflex responses to cold air. However, other investigators have not detected any changes in FEV 1 in response to nasal breathing of subfreezing air (20,23). This discrepancy may reflect different methods to cool the nose and to measure the bronchoconstriction.…”
Section: Cold Air-provoked Lower-airway Reflex Responsesmentioning
confidence: 80%
“…Even subfreezing air is almost completely saturated and warmed to near body temperature when it has passed the nasal cavity (15,18,19). Therefore, at rest and during light exercise the possible trigger sites for cold air-provoked respiratory symptoms include the facial skin and the nasal mucosa but not the lower airways (20).…”
Section: The Possible Trigger Sites For Cold Air-provoked Airway Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have suggested that facial cooling, and not nasal exposure, was responsible for the bronchoconstrictive effect of cold air. 69 Also, after nasal allergen provocation, no changes in FEV 1 values could be measured in patients with allergic rhinitis and asthma. 60,70 Nasal provocation with methacholine 71 and allergen 60,72 in patients with allergic rhinitis and asthma resulted in impaired airway function.…”
Section: Neural Pathwaymentioning
confidence: 99%
“…Breathing cold air causes the cooling of nasal and bronchial mucosa, seriously impairing ciliary motility and consequently reducing the immune system's resistance to respiratory infections [107,108]. Exposure to cold air may also increase the number of granulocytes and macrophages in the lower airways in healthy subjects [109] and induce bronchoconstriction [110,111], suggesting that cold exposure could be involved in the pathogenesis of the asthma-like condition. Part of the increase in respiratory outcomes during cold periods may also be attributed to cross-infections from increased indoor crowding during winter [112].…”
Section: Mechanisms and Vulnerable Subgroupsmentioning
confidence: 99%